Case report: is low α-Gal enzyme activity sufficient to establish the diagnosis of Fabry disease? - Gilson Biagini; Ana Clara Simões Flórido Almeida; Tammy Vernalha Rocha Almeida; Cassiano Augusto Braga Silva; Bruna Fernanda de Castro; Tais Cristina Reche; Ana Cláudia Dabinski; Fellype Carvalho Barreto (Brazilian Journal of Nephrology)
Abstract Fabry disease is an X-linked lysosomal storage disease due to alpha-galactosidase A (α-Gal A) deficient activity which leads to the accumulation of glucoesphingolipids, such as globotriaosilceramide. There are over 700 known mutations of the enzyme gene, and most of them cause Fabry Disease. This case report describes a hemodialysis patient with a rare and controversial GLA gene mutation, the D313Y. The medecial investigation confirmed that D313Y is an alpha-galactosidase A sequence variant that causes pseudo deficient enzyme activity in plasma but not Fabry disease. Thus, clinical symptoms that prompted Fabry disease investigation could not be attributable to Fabry disease and therefore enzyme replacement therapy was not indicated.